2016
DOI: 10.1371/journal.pone.0148221
|View full text |Cite
|
Sign up to set email alerts
|

The Symbiotic Performance of Chickpea Rhizobia Can Be Improved by Additional Copies of the clpB Chaperone Gene

Abstract: The ClpB chaperone is known to be involved in bacterial stress response. Moreover, recent studies suggest that this protein has also a role in the chickpea-rhizobia symbiosis. In order to improve both stress tolerance and symbiotic performance of a chickpea microsymbiont, the Mesorhizobium mediterraneum UPM-Ca36T strain was genetically transformed with pPHU231 containing an extra-copy of the clpB gene. To investigate if the clpB-transformed strain displays an improved stress tolerance, bacterial growth was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 62 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…More interestingly the symbiotic effectiveness of the clpB -overproducing strain increased ∼60% at pH 5 and ∼83% at pH 7, compared to the wild-type strain. This improved symbiotic phenotype may be related to an increased expression of symbiosis genes, as detected for the nodulation genes nodA and nodC [116].…”
Section: Rhizobia Improvement Using Stress Response Genesmentioning
confidence: 88%
See 1 more Smart Citation
“…More interestingly the symbiotic effectiveness of the clpB -overproducing strain increased ∼60% at pH 5 and ∼83% at pH 7, compared to the wild-type strain. This improved symbiotic phenotype may be related to an increased expression of symbiosis genes, as detected for the nodulation genes nodA and nodC [116].…”
Section: Rhizobia Improvement Using Stress Response Genesmentioning
confidence: 88%
“…The first successful improvement of a rhizobium with a chaperone gene was achieved using the chickpea nodulating strain M. mediterraneum UPM-Ca36 T modified with extra-copies of the clpB gene [116]. The nodulation kinetics analysis showed a higher rate of nodule development as well as a higher number of nodules in plants inoculated with the clpB -transformed strain.…”
Section: Rhizobia Improvement Using Stress Response Genesmentioning
confidence: 99%
“…Chickpea ( Cicer arietinum L.) was chosen for these experiments due to its importance in terms of a food legume crop and source of protein worldwide, whose production is limited by several biotic and abiotic stresses [44]. Moreover, two compatible mesorhizobia strains, namely Mesorhizobium ciceri LMS-1 [47] and M. mediterraneum UPM-Ca36 T [48] strains, were selected in order to evaluate whether the co-inoculation effect with the endophytic bacteria is dependent on the Mesorhizobium strain used. Based on plant growth-promoting characteristics, three pseudomonads strains, Pseudomonas sp.…”
Section: Methodsmentioning
confidence: 99%
“…Chickpea seeds were surface sterilized and germinated as described [48]. One seed was planted per plastic pot (±300 mL) previously filled with sterilized vermiculite.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the involvement of other bacterial genes in legume-rhizobia symbioses has been described. Some studies have shown that genes commonly found among prokaryotes and involved in a diversity of cellular mechanisms have also a role in legume- Rhizobium symbiosis, as, for example, stress response genes [68], quorum sensing, or secretion system genes [912].…”
Section: Introductionmentioning
confidence: 99%